2009
DOI: 10.1039/b908552a
|View full text |Cite
|
Sign up to set email alerts
|

Photocycloaddition of the T1 excited state of thioinosine to uridine and adenosine

Abstract: Novel photoadducts were obtained by irradiation of thioinosine (6-thiopurine riboside, TI) in deaerated aqueous solution without and in the presence of uridine and adenosine. Excitation (lambda > 300 nm) of TI to its excited S2 state yields a single bimolecular photoproduct. It is a purine-pyrimidine diriboside in which the purine ring is attached to the amide nitrogen of 6-amino-4-thioxo-5-formamidopyrimidine. When TI was irradiated in the presence of an excess of adenosine, two photoproducts were isolated: d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The self-quenching constants depend on the viscosity of the solvent, suggesting they are close to the diffusion-controlled limit [195]. Similar results were obtained more recently for 6-thiopurine [208] and 9-propyl-6-thiopurine [21] upon nanosecond laser excitation at 355 nm in aqueous buffer solution at pH 5.8. Attempts to determine the intersystem crossing rate constant of 6-thiopurine by using picosecond transient absorption spectroscopy (35 ps pulse duration) were unsuccessful [195] and the authors concluded that it must have a value greater than 1.3 Â 10 10 s À1 .…”
Section: Excited-state Deactivation Mechanism In 6-thiopurine Derivatsupporting
confidence: 77%
See 1 more Smart Citation
“…The self-quenching constants depend on the viscosity of the solvent, suggesting they are close to the diffusion-controlled limit [195]. Similar results were obtained more recently for 6-thiopurine [208] and 9-propyl-6-thiopurine [21] upon nanosecond laser excitation at 355 nm in aqueous buffer solution at pH 5.8. Attempts to determine the intersystem crossing rate constant of 6-thiopurine by using picosecond transient absorption spectroscopy (35 ps pulse duration) were unsuccessful [195] and the authors concluded that it must have a value greater than 1.3 Â 10 10 s À1 .…”
Section: Excited-state Deactivation Mechanism In 6-thiopurine Derivatsupporting
confidence: 77%
“…Excitation at 355 nm with 8 ns laser pulses results in the prompt population of the triplet state [13]. It was determined that nonradiative processes play a major role in the deactivation of the triplet state (Table 11), with a fraction of the triplet state population decaying by self-quenching (Table 17) [13], as observed previously in 6-thiopurine [195,208]. Based on the El-Sayed propensity rules [214,215] and on vertical excited-state calculations performed in acetonitrile at the CIS/CPCM/aug-cc-pVTZ level of theory, the authors proposed that intersystem crossing should occur from the S 1 (nπ*) state to the T 1 (ππ*) state upon direct excitation of the S 2 (ππ*) state, i.e., S 2 (ππ*) !…”
Section: Excited-state Deactivation Mechanism In 6-thiopurine Derivatmentioning
confidence: 93%
“…Similarly, the lowest‐energy absorption band of 6‐thio‐2′‐deoxyguanosine and 2′,3′,5′‐tri‐ O ‐acetyl‐6,8‐dithioguanosine redshifts by 90 (10 515 cm −1 ) and 130 nm (13 594 cm −1 ) relative to 2′‐deoxyguanosine , whereas that of S 6 ‐methylthioinosine and 6‐thioinosine redshifts by 42 (5796) and 71 nm (8911 cm −1 ) relative to inosine . A low‐energy absorption tail is also observed in the absorption spectra of 6‐thiopurine, 6‐thioguanine, 6‐thioinosine and 6‐thio‐2′‐deoxyguanosine that extends into the near‐visible region and that is redshifted in going from aqueous to organic solvents . Semi‐empirical , single‐reference and multiconfigurational calculations have consistently assigned the absorption tail to the S 0 → S 1 (n S π*) transition, while the lowest‐energy absorption band has been assigned to the S 0 → S 2 (π S π*) transition.…”
Section: Steady‐state Photophysical Propertiesmentioning
confidence: 96%
“…2 μs in 2‐propanol to ca. 5 μs in ethanol , while that of 6‐thioinosine ranges from 1.25 μs in aqueous solution at pH 5.8 to 3.2 μs in acetonitrile . An intrinsic triplet decay lifetime of 1.1 ± 0.1 μs has been reported for 6‐thio‐2′‐deoxyguanosine in aqueous solution , while the intrinsic triplet decay lifetimes of 6‐thioguanine and azathioprine have not been reported.…”
Section: Time‐resolved Photophysicsmentioning
confidence: 97%
See 1 more Smart Citation